Endovascular strategies for post-dissection aortic aneurysm (PDAA) - Zeng, Zhaoxiang (J Cardiothorac Surg, 2020)
Residual patent false lumen (FL) after type B aortic dissection (TBAD) repair is independently associated with poor long-term survival. Open surgery and endovascular repair result in good clinical outcomes in patients with AD. However, both treatments focus on proximal dissection but not distal dissection. About 13.4–62.5% of these patients present with different degrees of distal aneurysmal dilatation after primary repair. Although open surgery is the first-choice treatment for post-dissection aortic aneurysm (PDAA), there is a need for high technical demand since open surgery is associated with high mortality and morbidity. As a treatment strategy with minimal invasion, endovascular repair shows early benefits and low morbidity. For PDAA, the narrow true lumen (TL), rigid initial flap and branch arteries originating from FL have increased difficulties in operation. The aim of endovascular treatment is to promote FL thrombosis and aortic remodeling. Endovascular repair includes intervention from FL and TL sides. TL intervention techniques (parallel stent-graft, branched and fenestrated stent-graft among others) have been proven to be safe and effective in PDAA. Other FL intervention techniques that have been used in selected patients include FL embolization and candy-plug techniques. This article introduces available endovascular techniques and their outcomes for the treatment of PDAA.